Groundwater and Subsidence Modeling Combining Geological and Multi-Satellite SAR Data over the Alto Guadalentín Aquifer (SE Spain) - Pablo Ezquerro; Carolina Guardiola-Albert; Gerardo Herrera; José Antonio Fernández-Merodo; Marta Béjar-Pizarro; Roberta Bonì (Geofluids)
In the current context of climate change, improving groundwater monitoring and management is an important issue for human communities in arid environments. The exploitation of groundwater resources can trigger land subsidence producing damage in urban structures and infrastructures. Alto Guadalentín aquifer system in SE Spain has been exploited since 1960 producing an average piezometric level drop of 150 m. This work presents a groundwater model that reproduces groundwater evolution during 52 years with an average error below 10%. The geometry of the model was improved introducing a layer of less permeable and deformable soft soils derived from InSAR deformation and borehole data. The resulting aquifer system history of the piezometric level has been compared with ENVISAT deformation data to calculate a first-order relationship between groundwater changes, soft soil thickness, and surface deformation. This relationship has been validated with the displacement data from ERS and Cosmo-SkyMed satellites. The resulting regression function is then used as an empirical subsidence model to estimate a first approximation of the deformation of the aquifer system since the beginning of the groundwater extraction, reaching 1 to 5.5 m in 52 years. These rough estimations highlight the limitations of the proposed empirical model, requiring the implementation of a coupled hydrogeomechanical model.